Uso de sensor infrarrojo como nuevo método para la estimación de densidad de Oceanites oceanicus nidificantes en Antártida - Orgeira, José Luis (1997)
An infrared sensor, as a new method for localization of Wilson's Storm Petrel nests, was tested at Cierva Point, Gerlache Strait, in the Antarctic Peninsula. It detects the heat emitted by breeding birds benneath debris. To test its effectiveness, we used the sensor in an area where nests had already been located, finding 100% ofthe nests. Afterwards, seven eoastal sites with an average area of 548 m' were sampled. The infrared sensor was highly sensitive to the presence of birds benneath rocks; no obvious error sources were found. Besides providing reliable density values, the use of infrared sensors reduced the human impact on colonies because no traumatic methods were used for finding nests.